4=3(v+2)-5v

Simple and best practice solution for 4=3(v+2)-5v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=3(v+2)-5v equation:



4=3(v+2)-5v
We move all terms to the left:
4-(3(v+2)-5v)=0
We calculate terms in parentheses: -(3(v+2)-5v), so:
3(v+2)-5v
We add all the numbers together, and all the variables
-5v+3(v+2)
We multiply parentheses
-5v+3v+6
We add all the numbers together, and all the variables
-2v+6
Back to the equation:
-(-2v+6)
We get rid of parentheses
2v-6+4=0
We add all the numbers together, and all the variables
2v-2=0
We move all terms containing v to the left, all other terms to the right
2v=2
v=2/2
v=1

See similar equations:

| 2a+7=5a−5 | | –10d+9=–9d | | 7x+15=3x+4+4x | | 3(3y-7)=2y+7 | | 13x*12=1233 | | 4x+2=2x+6x+2 | | a+13=4a–38 | | f(-2)=4(-2)+10 | | 3/5=7/kk= | | 3(3y−7)=2y+7 | | 3^(x+2)=9^(x+1) | | 10/4=35/x | | X=2x-4x | | 7n+5(n+2)=10n+20 | | z−9=6 | | 14=-6+w | | 12x+5(14x-14)= | | -18+r=-25 | | -7u-7/4=3/4u-7/3 | | -4+b=-5+6b | | -25=f-18 | | a-7=23-2a | | x+27=30+89x | | 6+f=71-f | | 7(l−5)=21 | | 7p+8p-12=36 | | s-2=-6+3s | | -9+n=13-5n | | 7i−4=66 | | 3x-18=7x-44 | | 14+m=24-12+3m | | 2/5=3/z-2 |

Equations solver categories